Global Status of Bufavirus, Cosavirus, and Saffold Virus in Gastroenteritis: A Systematic Review and Meta-Analysis - Razizadeh, Mohammad Hossein; Khatami, Alireza; Zarei, Mohammad (Frontiers in Medicine, 2022)
Background: Bufavirus (BuV), Human Cosavirus (HCoSV), and Saffold (SAFV) virus are three newly discovered viruses and have been suggested as possible causes of gastroenteritis (GE) in some studies. The aim of present study was to estimate the overall prevalence of viruses and their association with GE. Methods: A comprehensive systematic search was conducted in Scopus, Web of Science, PubMed, and Google scholar between 2007 and 2021 to find studies on the prevalence of BuV, HCoSV, and SAFV virus. Result: Meta-analysis of the 46 included studies showed the low prevalence of BuV (1.0%, 95% CI 0.6–1.5%), HCoSV (0.8%, 95% CI 0.4–1.5%) and SAFV (1.9%, 95% CI 1.1–3.1%) worldwide. Also, no significant association between these viruses and GE was observed. BuV was isolated from GE patients in Africa, while SAFV was more common in Europe. BuV1 and BuV2 have the same prevalence between the three identified genotypes of BuV. HCoSV-C was the most prevalent genotype of HCoSV and SAFV2 was the commonest genotype of SAFV. All of these viruses were more prevalent in children older than 5 years of age. Conclusion: This was the first meta-analysis on the prevalence and association of BuV, HCoSV and SAFV with GE. While no significant association was found between infection with these viruses and GE, we suggest more studies especially, with case-control design and from different geographical regions in order to enhance our knowledge of these viruses.